Larangan Perkawinan Sesuku dalam Masyarakat Canduang; (Tinjauan Kemaslahatan dalam Hukum Islam) - Danil, Muhammad (Jurnal AL-AHKAM, 2019)
Intermarriage among one tribe is a model of marriage that is prohibited in custom. This marriage is used in Minangkabau society which almost entirely embraced Islam. However, this ban can survive from the very beginning until now as seen in the present day society. This study aims to find out what is the reason, the form of marriage restriction among citizens in one tribe and its legal consequences to Canduang’s society. In this study the writer uses the analysis of mashlaha in Islamic law for what reason of society’s inhibitions in prohibiting marriage among tribal people; how the form of kemashlahatan ban marriage between tribal people and how the consequences of marriage ban law among tribal people. This study shows that the reason for marriage ban among tribal people in the “canduang” society is a shame factor. This prohibition is used to prove that between one tribe’s relatives must be maintained for being a wider level of unity. Penalties imposed on offenders aimed at preventing fractures in the fraternal system within the tribe and continue to maintain a sil- aturrahmi tie between members of the Canduang community. The prohibition affects the strong sense of unity within the country. Either way, legal conse- quences, and forms of marriage restriction among tribal people are included in one form of mashlahah mursalah